2019
DOI: 10.15244/pjoes/89899
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Polycyclic Aromatic Hydrocarbons in Coal in China

Abstract: As China's main energy source, coal production and consumption account for 72% and 62%, respectively, of primary energy. The total output of raw coal was 3.41 billion tonnes (t) in 2016, down 9.0% from the same period a year earlier, and about 90% of coal comes from underground mines. In recent years, many coal mines have been closed because of the depletion of coal resources, resource integration, and coal mine production safety. Consequently, groundwater levels in these mines rise rapidly after the mine drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that, in the process of coal mining, the treatment and storage of coal provided the basic conditions for the release of PAHs into the environment [4][5][6][7][8][9]. For example, PAHs in coal and coal waste could be leached into the mine water [10] and then enter into the aquatic environment with the discharge of mine water [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that, in the process of coal mining, the treatment and storage of coal provided the basic conditions for the release of PAHs into the environment [4][5][6][7][8][9]. For example, PAHs in coal and coal waste could be leached into the mine water [10] and then enter into the aquatic environment with the discharge of mine water [11].…”
Section: Introductionmentioning
confidence: 99%
“…The PAHs release from solid matrices is most frequently carried out using extraction with organic solvents (benzene, toluene, acetone, methanol, hexane, acetonitrile, dichloromethane, chloroform, and their mixtures) in Soxhlet apparatus or an ultrasonic bath; The methods of PAHs extraction from solid samples that can be applied to extract PAHs from coal include supercritical fluid extraction, liquid extraction under pressure, microwave extraction, extraction with hot water [21][22][23][24].…”
Section: The Procedures Of Coal Sample Preparation For Pahs Content D...mentioning
confidence: 99%
“…The distribution of 16 PAHs in coal mined in China and the factors affecting this distribution were analyzed in [12]. Results showed that the average concentration of PAHs in the samples of raw coal was 10.540±7.973 μg/g, and PAHs with low molecular mass had the largest content, comprising 44% of the total PAHs concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), combustion condition and even burning stages of coal in the workshops. In the CP, the processes in the dry distillation of bituminous coals which have the highest concentration of 16-PAHs than lignite and anthracite [22] could yield PAHs emissions at a large scale and are the major contributors to the iron and steel industry. Coking wastewaters, oils and solid wastes produced during deep processing of tar and gas purification also contain high concentrations of PAHs.…”
Section: Distribution and Levels Of Pahsmentioning
confidence: 99%